Algorithm for Finding Singular Points of a General Algebraic Hypersurface - Lyapin, A. P.; Mikhalkin, E. N. (Programming and computer software, 2025)
In this paper, an algorithm for calculating the parameterization of the Horn–Kapranov -discriminant set and singular points of an algebraic hypersurface, using the Maple computer algebra system, is proposed.